Exceptional long-term survival in pulmonary large-cell neuroendocrine carcinoma with brain metastases: a case report - Liu, Bin; Zhang, Liangwen; Wang, Hua (Frontiers in Oncology, 2026)
BackgroundLarge-cell neuroendocrine carcinoma (LCNEC) of the lung is a rare and aggressive malignancy, with a poor prognosis and limited therapeutic options, particularly in advanced stages with brain metastases. Long-term survival in metastatic LCNEC is exceedingly uncommon.Case presentationWe report a case of a 32-year-old female diagnosed with stage IV pulmonary LCNEC in 2015. Over a 10-year disease course, she underwent a comprehensive, multimodal treatment approach, including chemotherapy, targeted therapy, two craniotomies, whole-brain radiotherapy, and resection of pelvic metastases. Serial imaging revealed prolonged stability of pulmonary lesions and dynamic control of brain metastases. Longitudinal monitoring of pro-gastrin-releasing peptide (PRO-GRP) levels showed a strong correlation with tumor progression. Molecular profiling identified RB1 and SDHD copy number loss, among other alterations. The patient remains alive 115 months after diagnosis and over 50 months after initial brain metastasis, representing one of the longest documented survivals in metastatic LCNEC.ConclusionThis case demonstrates that prolonged survival in stage IV LCNEC with brain metastases is possible through individualized multimodal therapy and close longitudinal monitoring. It underscores the potential value of molecular profiling and biomarkers like PRO-GRP in treatment planning and disease tracking.